2002
DOI: 10.1124/mol.62.5.1128
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Metal Chelator 2,3-Dimercapto-1-propanesulfonate with the Rabbit Multispecific Organic Anion Transporter 1 (rbOAT1)

Abstract: The metal chelator DMPS (2,3-dimercapto-1-propanesulfonate) is used to treat heavy metal intoxication because it increases renal excretion of these toxins, which are accumulated in proximal tubule cells. To evaluate the involvement of the organic anion transporter 1 (OAT1) in the renal flux of DMPS, we examined the effect of DMPS on transport mediated by the rabbit ortholog of OAT1 and compared these characteristics with those observed in intact isolated rabbit proximal tubules. The rabbit OAT1 (rbOAT1) cDNA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 28 publications
4
29
0
Order By: Relevance
“…Subsequent cloning attempts have led to the identification of the human ortholog, hOAT1, containing two functional splice variants, as well as orthologs from monkey, pig, rabbit, and Caenorhabditis elegans (Lopez-Nieto et al, 1997;George et al, 1999;Bahn et al, 2002;Hagos et al, 2002). The gene for hOAT1 (i.e., SLC22A6) is located on chromosome 11q12.3, very near the OAT3 gene, SLC22A8 (Eraly et al, 2003b) (Table 1).…”
Section: A Organic Anion Transporter 1 (Slc22a6)mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent cloning attempts have led to the identification of the human ortholog, hOAT1, containing two functional splice variants, as well as orthologs from monkey, pig, rabbit, and Caenorhabditis elegans (Lopez-Nieto et al, 1997;George et al, 1999;Bahn et al, 2002;Hagos et al, 2002). The gene for hOAT1 (i.e., SLC22A6) is located on chromosome 11q12.3, very near the OAT3 gene, SLC22A8 (Eraly et al, 2003b) (Table 1).…”
Section: A Organic Anion Transporter 1 (Slc22a6)mentioning
confidence: 99%
“…Early Northern blot analyses have revealed that OAT1/ Oat1 transcripts are strongly expressed in human kidney as well as kidneys of monkeys, dogs, sheep, pigs, rabbits, rats, and mice (Lopez-Nieto et al, 1997;Sweet et al, 1997;Lu et al, 1999;Bahn et al, 2002;Hagos et al, 2002;Tahara et al, 2005b;Wood et al, 2005;Bleasby et al, 2006). Immunohistological studies have revealed the expression of hOAT1 and rat and mouse Oat1 at the basolateral membrane of proximal tubule kidney cells (Sekine et al, 1997;Hosoyamada et al, 1999).…”
Section: A Organic Anion Transporter 1 (Slc22a6)mentioning
confidence: 99%
“…The extraction of Hg 2ϩ from renal tubular cells does not appear to involve glomerular filtration but rather a direct secretory process whereby Hg 2ϩ moves from peritubular blood into the tubular lumen Zalups et al, 1998). It is well documented that reduced and oxidized forms of DMPS (but not DMPS S-conjugates of Hg 2ϩ ) are taken up by the organic anion transporter 1 in the basolateral membrane of proximal tubular cells (Zalups et al, 1998;Islinger et al, 2001;Bahn et al, 2002). DMSA, however, appears to be taken up by the sodium-dependent dicarboxylate transporter, which is also localized in the basolateral membrane of these cells .…”
mentioning
confidence: 99%
“…Although the rabbit orthologs of OCT1, OCT2, and OAT1 have been cloned (3,49,57), rbOAT3 had to be cloned and was found to share the general transport properties noted previously for the human (10), rat (30,46), and mouse (47) orthologs of OAT3, most notably a broad substrate specificity ( Fig. 1) and the capacity to mediate OA/dicarboxylate exchange (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Stable expression of transport activity was verified by visual inspection of mediated accumulation of 6CF. In some experiments, transport activity was measured after transient transfection of rbOAT3 (in pcDNA3.1) into COS-7 cells, or of rbOAT1 into CHO cells, as described previously (3,22).…”
Section: Methodsmentioning
confidence: 99%